Loan to Deposit Ratio, Capital Adequacy Ratio, Non Performing Loan, Size dan Return On Assets Bank Perkreditan Rakyat di Provinsi Daerah Khusus Ibukota Jaya - Erni Yulianti; Muhammad Yusuf (Magister Akuntansi Universitas Pancasila, 2018)
ABSTRACT This study aims to examine and analyze the effect of loan to deposit ratio, capital adequacy ratio, non performing loan and size to return on assets in rural bank of special areas of the capital jaya province, registered at bank Indonesia period of december 2015-december 2016. Sample which is used in this research as many as 13 rural banks that routinely report its progress to bank Indonesia. The results showed that the loan to deposit ratio and capital adequacy ratio did not affect the return on assets. Non-performing loans negatively affect return on assets, while the size has a positive effect on return on assets. Future research can be re-tested by adding the variable because the ability of independent variables affect the return on assets is moderate, so it is still possible to add variables in the model. The sample can be expanded for rural banks in Indonesia so that the results can be generalized to all rural banks in Indonesia. ABSTRAK Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh loan to deposit ratio, capital adequacy ratio, non performing loan dan size terhadap return on assets pada bank perkreditan rakyat wilayah provinsi daerah khusus ibukota jaya, yang terdaftar di bank Indonesia periode triwulan bulan desember 2015-desember 2016. Sampel yang digunakan dalam penelitian ini sebanyak 13 bank perkreditan rakyat yang secara rutin melaporkan perkembangannya pada bank Indonesia. Hasil penelitian menunjukkan bahwa loan to deposit ratio dan capital adequacy ratio tidak berpengaruh terhadap return on assets. Non performing loan berpengaruh negatif terhadap return on asset, sedangkan size berpengaruh positif terhadap return on asset. Riset mendatang dapat dilakukan pengujian ulang dengan menambah variabel karena kemampuan variabel independent mempengaruhi return on assets tergolong sedang, sehingga masih dimungkinkan menambah variabel di dalam model. Sample dapat diperluas untuk bank perkreditan rakyat di Indonesia agar hasil penelitian dapat digeneralisasi untuk seluruh bank perkreditan rakyat di Indonesia. JEL Classification: G21, M40, L25